Environmental sanitation in peri-urban ger areas in the city of Darkhan (Mongolia): A description of current status, practices, and perceptions - Katja Sigel (Helmholtz-Zentrum für Umweltforschung (UFZ), 2010)
This report describes the results of a household survey conducted in September 2009 in a selected peri-urban subdistrict (bag) in Darkhan city. A total number of 139 randomly selected households were surveyed about the current status of environmental sanitation, including water supply, sanitation, stormwater management and solid waste management. Special focus was placed on socio-economic issues, the environmental sanitation practices and perceptions of the ger residents, and their attitudes towards and demand for improved environmental sanitation services. The results of the household survey are embedded in further research work assessing the water and sanitation sector in Darkhan city, Darkhan-Uul aimag and Mongolia, specifically in regard to peri-urban ger areas. The results reveal a problematic situation: Due to improved access to safe drinking water, water consumption and the corresponding wastewater have increased, leading to environmental degradation and potential health risks. Greywater is discharged untreated into greywater holes, open drainage channels or on open fields. Self-built unsealed pit latrines without cleanouts are used on every household's compound. Thus urine and faeces leak into the ground. Stormwater is collected in a perfunctory manner which can lead to stormwater flooding in the rainy season. Most of the interviewees were quite aware of these problems and were willing to contribute towards improvements. From the point of view of the ger residents, sanitation is the most pressing issue they face, followed by water supply, solid waste management and stormwater management. – – 2009 o 9 apxa xo aa a a. 139 a aa aa a aa oo a , , , ooo eeee, o aaa aa a. aa a o , o aaa oo, a a aaa . apxa xo, aa- aa oo oo , a oo o a aa a aa. aa a aaa a a a. aaaaa oooo o . aa o, oo a. A oo o oo o , ooo aa aa aa a aa a. a ooo. a oo . ooo a aaa ooo ep ooo . aa aa ooo a aaa a aa aaa a. o o aaa aa a. aaa a, o oo ooo ooo o a.
Keywords: 330; Mongolia; environmental sanitation; peri-urban ger areas; household survey; current status; practices; perceptions; Moo; a; ep-; a aa aa